Pilot-scale bioconversion of rice and sunflower agro-residues into medicinal mushrooms and laccase enzymes through solid-state fermentation with Ganoderma lucidum - Postemsky, Pablo Daniel (2017)
Solid-state fermentation was evaluated at the pilot-scale for the bioconversion and valorization of rice husks and straw (RSH), or sunflower seed hulls (SSH), into medicinal mushrooms and crude extracts, with laccase activity. The average mushroom yield was 56 kg dry weight per ton of agro-residues. Laccase activity in crude aqueous extracts showed its maximum value of 10,927 U kg−1in RSH (day 10, Exudate phase) and 16,442 U kg−1in SSH (day 5, Full colonization phase), the activity at the Residual substrate phase being 511 U kg−1in RSH and 803 U kg−1in SSH, respectively. Crude extracts obtained with various protocols revealed differences in the extraction yields. Lyophilization followed by storage at 4 °C allowed the preservation of laccase activity for more than one month. It is proposed that standard mushroom farms could increase their profits by obtaining laccase as a byproduct during the gaps in mycelium running.